THE EFFECT OF PERMISSIVE PARENTING AND ISLAMIC UNDERSTANDING ON THE MORALS OF MADRASAH ALIYAH STUDENTS - Uswatun Hasanah; Nefi Darmayanti; Junaidi Arsyad (Pusat Penerbitan Universitas (P2U) Unisba, 2022)
The purpose of this study is to investigate the effect of permissive parenting and Islamic understanding on the morals of Madrasah Aliyah students at the Darul Qur'an Islamic boarding school in the Medan Tembung sub-district. This study used a quantitative technique with a phenomenological approach. Observation, questionnaires/surveys, and documentation are used in data collection techniques. Analysis requirements testing, multiple linear test analysis, partial hypothesis testing (t), and simultaneous hypothesis testing are some of the data analysis approaches employed (f). The findings of this study demonstrated that permissive parenting (X1) had a substantial influence on student morality (Y) at Madrasah Aliyah Darul Qur'an Medan Tembung District, as evidenced by a value of 0.023 <0.05 and a t count of -1.990 > t table 1.988 so that it can be concluded that the first hypothesis is accepted, meaning that there is an influence of permissive parenting (X1) on student morals (Y). There is a significant influence between Islamic religious understanding (X2) and student morals (Y) Madrasah Aliyah Darul Qur'an, Medan Tembung District, as evidenced by a value of 0.025 > 0.05 and a t count value of 2.911 > 1.988 it can be concluded that the second hypothesis is accepted, meaning that there is an influence of Islamic religious understanding (X2) on student morals (Y). Permissive parenting (X1) and comprehension of Islam (X2) have a substantial effect on student morals (Y) in Madrasah Aliyah Darul Qur'an Medan Tembung District. Based on the output value, it is known that the coefficient of 0.191 is equal to 19.10 R Square of 0.036, this implies that the influence of the permissive parenting variable (X1) and understanding of Islam (X2) simultaneously on variable Y is 36%, the rest is influenced by other variables not included in this study.